Dimensões exclusoras e transformadoras no processo de trabalho dos profissionais de saúde de Unidades de Saúde da Família no apoio ao aleitamento materno exclusivo - Targino, Daniela Aparecida Salgado (Universidade Federal de São Carlos, 2013)
The Estratégia de Saúde da Família (ESF) (In English: The Family Health Strategy) is presented as a substitutive model to health care, according to the principles of the Sistema Único de Saúde (In English: the Unified Health System). It is a strategy that provides a comprehensive care to family, not only for intense situations but also for chronic deseases, with the objective of promoting and keeping health. Therefore, although the ESF is, in effect, a viable tool for the support and promotion of the Aleitamento Materno Exclusivo (AME) (In English: Exclusive Maternal Breastfeeding) health professionals should be willing to assume a dialogical approach with users that shares scientific knowledge and experiences. Therefore, the promotion and support of AME is the focus of this study, with the ESF as a research field. The goal was to analyze the exclusionary and transformative components of the work process in the family health care teams to support exclusive maternal breastfeeding. The Theoretical Framework used was constituted by the Dialogic Learning and the Dialogic Feminism and the methodological framework by the Critical Communicative Methodology. This is a qualitative study, developed with the staff of five family health units in a town in Minas Gerais, in 2011 and 2012. Data were collected using the technique of Communicative focus groups, and analyzed according to the Critical Communicative Methodology, highlighting the transformative and the exclusionary aspects regarding the support that the ESF provides to the AME. Results allowed to conclude that, within the category "Personal Experiences with the Maternal Breastfeeding transformative elements are more present than the exclusionary ones, showing that when the time of breastfeeding is longer than six months, a greater certainty exists regarding the orientations for the promotion and support of the maternal breastfeeding. In the category of "Promoting and supporting maternal breastfeeding", exclusionary elements were more present, demonstrating that even though the ESF is a reference in the support the AME, it is still influenced by an instrumental rationality, that gives place to care practices of little success. This influence creates obstacles for dialogic educational practices to favor transformation. The dialogue between researcher and participants provided by the communicative focus group allowed consensus about the fact that the promotion and support of the AME should emerge from a transformation regarding the way health orientations are performed. Therefore, the assumption of an egalitarian dialogue; in which breastfeeding is recognized in the social and cultural contexts of those who live it, respecting their knowledge and experiences and looking for the transformation of these contexts; should be present.
Keywords: Enfermagem; Aleitamento materno; Programa Saúde da Família (Brasil); Prática de saúde; Aprendizagem; Feminismo; Estratégia de Saúde da Família; Conhecimentos; Atitude e Prática em Saúde; Breastfeeding; Family health strategy; Knowledge, Attitude and practice in health; Learning; Feminism; CIENCIAS DA SAUDE::ENFERMAGEM